ANALISIS SINTAKSIS KALIMAT MAJEMUK DALAM TEKS BERITA PADA MEDIA DARING KOMPAS.COM - Nabila Rahma Aulia; Muhammad Ihsan Hayatul Barokah; Erlina Nur Fajriyanti; Asma Izzati; Iis Lisnawati (Jurnal Bastra (Bahasa dan Sastra), 2025)
This study aims to analyze the syntactic structure of compound sentences in online news texts on Kompas.com media. Using qualitative descriptive methods, this study identifies the structure, types, and functions of compound sentences in the news text entitled "Ghifran's Story, MAN 4 Jakarta Student Accepted by 13 Overseas Campuses". The results of the study show a variety of compound sentence structures used, including compound sentences with equivalent relationships of selection and addition, compound sentences with tiered relationships of concession, time, and purpose, and mixed compound sentences. The use of conjunctions such as "which", "or", "for", "and", "although", "since", "during", "that", and "and" plays an important role in connecting clauses logically. Compound sentences function to combine equivalent information, explain logical relationships between information, and build a structured flow of information. The study concludes that the use of compound sentences is not just a variation of sentence structure, but also a linguistic strategy that supports the clarity, completeness, and appeal of news texts in the context of online journalism.